Nilai-Nilai Moral yang Tercermin dalam Cerita Rakyat Legenda Bukit Perak - Thaariq, Muhammad (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the moral values contained within book of folklore legends of the silver hill by Ricky A. Manik. This type of research uses qualitative method with a descriptive approach. Data collection techniques used the research uses book text analysis techniques, namely reading, listening and taking notes using a research instrument in the form of a research data classification table. Analysis techniques the data used in this research is a descriptive interactive data analysis technique, starting from the data reduction stage, data presentation and drawing conclusions. Results of this research shows that there are moral values reflected in legendary folklore books silver hill. The form of moral values obtained will be in the form of quotes about moral values man's relationship with God, man's relationship with himself, relationship humans with humans, the relationship between humans and nature. Based on the research results It was found that the moral value with the most quotes concerns the moral value of relationships man and himself, there were 42 quotes obtained. Then moral values which has few quotes and nothing at all regarding the moral value of relationships humans and nature found 2 quotes and the relationship between humans and their God not a single moral value was found regarding this moral value.Keywords: Analysis, moral values, folklore, legends.